Membrane remodelling by a lipidated endosomal sorting complex required for transport-III chimera, in vitro. Issue 5 (6th October 2018) - Marklew, C. J.; Booth, A.; Beales, P. A.; Ciani, B.
Abstract : The complexity of eukaryotic cells is underscored by the compartmentalization of chemical signals by phospholipid membranes. A grand challenge of synthetic biology is building life from the 'bottom-up', for the purpose of generating systems simple enough to precisely interrogate biological pathways or for adapting biology to perform entirely novel functions. Achieving compartmentalization of chemistries in an addressable manner is a task exquisitely refined by nature and embodied in a unique membrane remodelling machinery that pushes membranes away from the cytosol, the ESCRT-III (endosomal sorting complex required for transport-III) complex. Here, we show efforts to engineer a single ESCRT-III protein merging functional features from its different components. The activity of such a designed ESCRT-III is shown by its ability to drive the formation of compartments encapsulating fluorescent cargo. It appears that the modular nature of ESCRT-III allows its functional repurposing into a minimal machinery that performs sophisticated membrane remodelling, therefore enabling its use to create eukaryotic-like multi-compartment architectures.